Injuries among Korean female professional golfers: A prospective study - Joeng, H. S.; Na, Y. M.; Lee, S. Y.; Cho, Y. J. (Journal of Sports Science & Medicine, 2018)
This study aims to analyze the incidence, location, type, and mechanisms of injuries and possible injury risk factors among all levels of Korean female professional golfers. This was a prospective study with a follow-up period of 24 months. A total of 363 members of the Korean Ladies Professional Golf Association (KLPGA), who competed in tournaments during the 2015 and 2016 seasons, took part in the study. The incidence of injury varied by tournament level and was significantly higher in Division II (11.1/1000AEs) and Division III (13.4/1000AEs) than in Division I (5.6/1000AEs) (p < 0.05). The most common location and type of injury were the shoulder/clavicle (Division I: 14.1%, Division II: 15.7%, Division III: 17.3%) and the tendinosis or tendinopathy (21.2%) (Division I: 23.7%, Division II: 21.2%, Division III: 18.5%), respectively. The most common mechanism of injury was the golf swing (47.9%-51.6% for the three divisions), and the most frequent specific phase of injury was upon ball impact (23.5%-30.9%). Multivariate analysis revealed that body mass index and the number of previous season competitions were significantly associated with injury risk in female golfers. The other factors examined did not have a significant association with golf-related injuries. In conclusion, KLPGA golfers were commonly exposed to injuries and showed a higher rate of injuries in competitions than practices, with significantly higher in Division II, III than Division I. However, overall, there was no significant difference in the location, type, mechanism and risk factors for injuries among the division level of KLPGA.